2020
DOI: 10.1111/cts.12739
|View full text |Cite
|
Sign up to set email alerts
|

Semimechanistic Modeling to Guide Venetoclax Coadministration with Ritonavir and Digoxin

Abstract: Venetoclax is a cytochrome P450, family 3, subfamily A (CYP3A) substrate and was shown to inhibit P-gp efflux transporters in vitro. To quantify the impact of CYP3A inhibition by ritonavir on venetoclax disposition and P-gp inhibition by venetoclax on digoxin pharmacokinetics, two semimechanistic drug-drug interaction (DDI) models of venetoclax were developed using clinical data from healthy volunteers who received subtherapeutic doses of venetoclax with ritonavir 50-100 mg or digoxin 0.5 mg. These models were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
(36 reference statements)
2
7
0
Order By: Relevance
“…In a PBPK model, estimates of venetoclax exposures (AUC ∞ ) were 100%–385% higher in the presence of moderate CYP3A inhibitors and 480%–680% higher in the presence of strong CYP3A inhibitors 48 . In this model, the label recommended venetoclax dose reductions of at least 50% and 75% when coadministered with moderate and strong CYP3A inhibitors, respectively, 10 maintained venetoclax exposures between therapeutic and maximally achieved safe doses, similar to the result observed in a semi‐mechanistic model 43 …”
Section: Drug–drug Interactionssupporting
confidence: 64%
See 1 more Smart Citation
“…In a PBPK model, estimates of venetoclax exposures (AUC ∞ ) were 100%–385% higher in the presence of moderate CYP3A inhibitors and 480%–680% higher in the presence of strong CYP3A inhibitors 48 . In this model, the label recommended venetoclax dose reductions of at least 50% and 75% when coadministered with moderate and strong CYP3A inhibitors, respectively, 10 maintained venetoclax exposures between therapeutic and maximally achieved safe doses, similar to the result observed in a semi‐mechanistic model 43 …”
Section: Drug–drug Interactionssupporting
confidence: 64%
“…48 In this model, the label recommended venetoclax dose reductions of at least 50% and 75% when coadministered with moderate and strong CYP3A inhibitors, respectively, 10 maintained venetoclax exposures between therapeutic and maximally achieved safe doses, similar to the result observed in a semi-mechanistic model. 43 A common issue with patients with hematological malignancies is the need for multiple therapies to address comorbidities or side effects from cancer treatments. Using PBPK and popPK to investigate whether additional dose adjustments were needed in patients taking multiple strong CYP3A inhibitors concomitantly, it was found that venetoclax exposures were similar to that of just taking one strong CYP3A inhibitor.…”
Section: Effect Of Cyp3a Inhibitors On Venetoclaxmentioning
confidence: 99%
“…Our analysis was based on a comprehensive absorption data set that included a broad spectrum of human fraction absorbed (fa) values for approximately 1000 compounds, , rodent faFg values for over 10,000 compounds, and about 3000 compounds with measured EPSA, noting that there was some overlap among the three data sets (Figure A). In this context, we evaluated ∼1000 AbbVie tool PROTACs, ∼2000 bRo5s, and ∼7000 Ro5s, with 36 external compounds (inclusive of approved drugs, clinical candidates, and tool compounds).…”
Section: Methodsmentioning
confidence: 99%
“…13,14 Venetoclax is predominantly metabolized by the CYP3A4 enzyme. 15,16 The relationship between venetoclax exposure and clinical responses has been previously desrcibed. [17][18][19][20] However, venetoclax absolute bioavailability has not been assessed.…”
Section: Accepted Articlementioning
confidence: 99%
“… 6 , 7 , 8 , 9 , 10 , 11 , 12 Venetoclax reaches C max 6–8 h after dosing, and has a terminal half‐life of 16 h. 13 , 14 Venetoclax is predominantly metabolized by the CYP3A4 enzyme. 15 , 16 The relationship between venetoclax exposure and clinical responses has been previously described. 17 , 18 , 19 , 20 However, venetoclax absolute bioavailability has not been assessed.…”
Section: Introductionmentioning
confidence: 99%